Strengthening Cooperative Business Performance through Human Resource Economics: The Effect of Workload, Work Environment, and Compensation on Employee Productivity - Suardika, I Ketut; Budiarta, Putu Riski (International Journal of Economics Development Research (IJEDR), 2025)
This study aims to examine the effect of workload, work environment, and compensation on employee performance, both partially and simultaneously, at Koperasi Simpan Pinjam (KSP) Karya Abadi in Buleleng. Employee performance has become a critical focus due to inconsistent achievement of monthly work targets and indications of imbalance between workload and received compensation. Adopting a quantitative approach, the study involved all 30 employees of KSP Karya Abadi as the research sample, using a census sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression with the help of SPSS 25.0. The findings reveal that workload has a negative and significant effect on employee performance, while work environment and compensation each have a positive and significant effect. Simultaneously, all three variables significantly influence employee performance. These results underscore the importance of balanced workload management, a supportive work environment, and fair compensation as key factors in enhancing employee productivity and, consequently, strengthening cooperative business performance.